1998
DOI: 10.1074/jbc.273.3.1273
|View full text |Cite
|
Sign up to set email alerts
|

NHE-RF, a Regulatory Cofactor for Na+-H+Exchange, Is a Common Interactor for Merlin and ERM (MERM) Proteins

Abstract: We have identified the human homologue of a regulatory cofactor of Na -H؉ exchanger NHE3 to which it is thought to bind via one of its two PDZ domains. The carboxyl-terminal region of NHE-RF, downstream of the PDZ domains, interacts with the amino-terminal protein 4.1 domain-containing segment of merlin in yeast twohybrid assays. This interaction also occurs in affinity binding assays with full-length NHE-RF expressed in COS-7 cells. NHE-RF binds to the related ERM proteins, moesin and radixin. We have locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
178
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(182 citation statements)
references
References 31 publications
2
178
0
2
Order By: Relevance
“…Negative regulation of CD44-HA interaction provides a mechanism that underlies the tumor-suppressor function of merlin Like the ERM proteins, merlin binds to several membrane-associated proteins, including CD44 (Tsukita et al, 1994;Sainio et al, 1997), NHE-RF/EBP50 (Murthy et al, 1998), and b1-integrin (Obremski et al, 1998). ERM proteins play important roles in organizing the actincytoskeleton which is essential for cell adhesion and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Negative regulation of CD44-HA interaction provides a mechanism that underlies the tumor-suppressor function of merlin Like the ERM proteins, merlin binds to several membrane-associated proteins, including CD44 (Tsukita et al, 1994;Sainio et al, 1997), NHE-RF/EBP50 (Murthy et al, 1998), and b1-integrin (Obremski et al, 1998). ERM proteins play important roles in organizing the actincytoskeleton which is essential for cell adhesion and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our findings suggest that EBP50 may contribute to the E-cadherin/b-catenindependent intercellular adhesion by acting directly on EGFR signaling output. Curto et al (2007) demonstrated that merlin/Nf2 tethers EBP50 to the cell cytoskeleton (Murthy et al, 1998) and thereby participates in the stabilization of AJs through the regulation of EGFR. The observation that EBP50, but not merlin/ Nf2, interacts directly with EGFR (Lazar et al, 2004;Takahashi et al, 2006;Curto et al, 2007), suggests that EBP50 regulates EGFR signaling per se.…”
Section: Loss Of Ebp50-egfr Interplay In Biliary Carcinomamentioning
confidence: 99%
“…Merlin constructs representing full-length (aa 1-595), amino terminus (aa 1-340) and carboxy terminus (aa 341-595) of isoform 1 were used as baits to screen a human fetal frontal cortex interaction library as previously described (Murthy et al, 1998). The cDNA clone obtained (aa 13-178) from this screen was referred to as MerIntA.…”
Section: Molecular Cloning Of Magicinmentioning
confidence: 99%
“…Full-length (aa 1-577), amino terminus (aa 1-332) and carboxy terminus (aa 307-577) of human moesin were expressed as GST fusion proteins using the vector pGEX4T1 (Amersham Biosciences). Expression and purification of all the GST fusion proteins were performed as described previously (Murthy et al, 1998). To generate GST-magicin fusion protein, magicin (aa 13-178) was cloned into pGEX-4T1, expressed and purified as for merlin.…”
Section: Dna Constructs and Expression In Escherichia Colimentioning
confidence: 99%
See 1 more Smart Citation